Penguatan Toleransi Melalui Kampung Moderasi Beragama Untuk Membangun Ketahanan Ideologi Pancasila Di Daerah Istimewa Yogyakarta - Shofa, Abd. Mu’id Aris; Alfaqih, Mifdal Zusron; Wafa, Alfian Fawaidil; Widiatmaka, Pipit (Jurnal Penelitian Agama Hindu, 2025)
Diversity in society, whether in terms of religion, language, ethnicity, tribe, and so on, is an unavoidable fact, especially for the Indonesian people. Therefore, this diversity must be managed and accommodated effectively to prevent it from becoming a threat that could lead to vertical or horizontal conflict. This research aims to. 1) finding out the pattern of strengthening tolerance in religious moderation villages in the Special Region of Yogyakarta, 2) finding out local actors involved in strengthening tolerance in religious moderation villages in the Special Region of Yogyakarta, and 3) finding out the implications for the resilience of Pancasila ideology in the Special Region of Yogyakarta. This study uses a qualitative approach with a descriptive research method. The data collection technique in this study used in-depth interviews, participatory observation, and documentation. The data validity test used was data triangulation, and the triangulation of data analysis methods and techniques used was interactive data analysis. The results of the study show that the pattern of strengthening religious tolerance is carried out by the village government in collaboration with religious leaders and community leaders by organizing Pancasila birthday gadgets (June 1), regular interfaith dialogues, and involving religious leaders in various activities. Local actors involved in strengthening tolerance in religious moderation villages are village heads, hamlet heads, religious leaders, community leaders, and youth leaders. Strengthening tolerance through religious moderation in villages has implications for increasing the resilience of Pancasila ideology in the Special Region of Yogyakarta, considering that the religious level of the community is increasing, and the harmony of life between religious people increases.